Developing sustainable security: police intelligence in post-conflict reconstruction. Issue 2 (2nd July 2016) - Evans, Sean M.
ABSTRACT: A new paradigm is needed to assist practitioners and academics alike in analysing, solving and managing the problems associated with post-conflict reconstruction. This paradigm should focus on disarming the warring factions through a comprehensive political settlement rather than forcing peace solely by way of military dominance. This can be done by making greater use of intelligence and security policy and programs in predicting future events and effectively deploying resources to train forces in a reconstruction environment. Also, combining foreign and domestic intelligence and police action provides the nexus for a sustainable defence strategy locally and globally. This strategy can be enhanced by the meshing and synchronisation of best management practices with a proactive managerial philosophy that understands and appreciates the utility of intelligence and special operations capacity within law enforcement.